Effects of a Covert Infection with Phthorimaea operculella granulovirus in Insect Populations of Phthorimaea operculella - Andreas Larem; Saoussen Ben Tiba; Eva Fritsch; Karin Undorf-Spahn; Jörg T. Wennmann; Johannes A. Jehle (Viruses, 2019)
Virus infections of insects can easily stay undetected, neither showing typical signs of a disease, nor being lethal. Such a stable and most of the time covert infection with Phthorimaea operculella granulovirus (PhopGV) was detected in a Phthorimaea operculella laboratory colony, which originated from Italy (Phop-IT). This covert virus (named PhopGV-R) was isolated, purified and characterized at the genetic level by full genome sequencing. Furthermore, the insect colony Phop-IT was used to study the crowding effect, double infection with other PhopGV isolates (CR3 and GR1), and co-infection exclusion. An infection with a second homologous virus (PhopGV-CR3) activated the covert virus, while a co-infection with another virus isolate (PhopGV-GR1) led to its suppression. This study shows that stable virus infections can be common for insect populations and have an impact on population dynamics because they can suppress or enable co-infection with another virus isolate of the same species.